Compound Journal Entries in Early Treatises on Bookkeeping. - Yamey, Basil S. (The Accounting Review, 1979)
Abstract ABSTRACT: This article traces references to and illustrations of compound journal entries in accounting or bookkeeping treatises up to Lodovico Flori's Trattato of 1636. It is shown that the practice was referred to, discussed, or illustrated earlier and more frequently than has been supposed.